Enhancing HIV Testing Coverage: Workplace HIV Self-Testing Initiative - Thoriq Abi Pramana (BKM Public Health and Community Medicine, 2024)
Objective: This initiative was carried out to compare the existing HIV screening program and proposed HIV-Self testing at the workplace program. This policy is expected to complement the current HIV screening program to increase HIV case detection in unreachable cases. Ministry of Health report on HIV in 2022 showed an appealing result obtained from a limited implementation of HIVST that the majority of clients (83%) were those who were undergoing HIV screening for the first time, so this pilot shows that HIVST is quite effective in reaching sub-populations that HIV testing services have never reached. Recommended by WHO, HIVST at the workplace may increase the uptake of HIV testing by offering workers greater confidentiality and autonomy and saving time for workers and healthcare providers. Hence, adopting HIVST at the workplace is one of the best options to reach a 90-90-90 cascade in Indonesia. Content: This initiative is supported by a comprehensive education campaign, test kit training, and counselling and support services for those in need. The program's goal is to reduce HIV-related stigma, raise HIV/AIDS awareness, and discover undiagnosed HIV cases in the workplace. These activities contribute to a better awareness of HIV/AIDS, a reduction in stigma and prejudice, the finding of undiagnosed cases, improved access to care and support, and a lower load on the healthcare system. Stigma and discrimination, restricted accessibility, knowledge, privacy issues, and resource availability are all challenges. Nonetheless, enablers include leader support, access flexibility, staff education and awareness, post-test counselling and assistance, and continous evaluation and modification. Thus, workplace HIV self-testing (HIVST) programs provide an innovative approach and potential to be an effective tool in community-wide HIV/AIDS prevention and management efforts.